Dance for Your Health: Exploring Social Latin Dancing for Community Health Promotion. Issue 3 (4th May 2017) - Iuliano, Joseph E.; Lutrick, Karen; Maez, Paula; Nacim, Erika; Reinschmidt, Kerstin
ABSTRACT: The goal of Dance for Your Health was to explore the relationship between social Latin dance and health as described by members of the Tucson social Latin dance community. Social Latin dance was selected because of the variety of dances, cultural relevance and popularity in Tucson, and the low-key, relaxed atmosphere. Dance has been prescribed to help manage diseases such as Parkinson's; however, not much is known about the use of dance for health promotion. Through qualitative methodologies, the project focused on the role dance can play in health promotion and in creating community connections. The project explored personal stories and experiences on the broader impact of health, the meaning of community from the social Latin dancer's point of view, thoughts on how social Latin dancing could be applied to help people in the community live healthier lives, and how to demystify social Latin dancing for people who are not currently dancing.